Are USDA reports still news to changing crop markets?. (April 2019) - Karali, Berna; Isengildina-Massa, Olga; Irwin, Scott H.; Adjemian, Michael K.; Johansson, Robert
Highlights: Changes in the relevance of USDA information in crop markets are investigated. Magnitude of market surprises and price reactions to those surprises are estimated. The size of market surprises remained stable over time. Price reaction to most reports increased post 2007. Enhanced value of public information is implied in markets with structural changes. Abstract: This study investigates whether major USDA reports still provide important news to changing crop markets. The news component of each report, or market "surprise, " is measured as a difference between the USDA estimate and its private expectation in corn, soybeans, and wheat markets. Changes in the relevance of USDA information are assessed by examining changes in the magnitude of market surprises and shifts in the futures price reaction to these surprises, which isolates the impact of each report. The stable size of market surprises over time suggests that competition from alternative data sources has not reduced the news component of USDA crop reports. Increasing price reaction to most reports, including those facing competition from alternative information sources, suggests that value of public information may be enhanced in uncertain markets affected by structural changes.